Tissue-specific expression of a gene encoding a cell wall-localized lipid transfer protein from Arabidopsis - Thoma, S; Hecht, U; Kippers, A; Botella, J; Vries, S. de; Somerville, C (Plant physiology (Bethesda), 1994)
Nonspecific lipid transfer proteins (LTPs) from plants are characterized by their ability to stimulate phospholipid transfer between membranes in vitro. However, because these proteins are generally located outside of the plasma membrane, it is unlikely that they have a similar role in vivo. As a step toward identifying the function of these proteins, one of several LTP genes from Arabidopsis has been cloned and the expression pattern of the gene has been examined by analysis of the tissue specificity of beta-glucuronidase (GUS) activity in transgenic plants containing LTP promoter-GUS fusions and by in situ mRNA localization. The LTP1 promoter was active early in development in protoderm cells of embryos, vascular tissues, lignified tips of cotyledons, shoot meristem, and stipules. In adult plants, the gene was expressed in epidermal cells of young leaves and the stem. In flowers, expression was observed in the epidermis of all developing inflorescence and flower organ primordia, the epidermis of the siliques and the outer ovule wall, the stigma, petal tips, and floral nectaries of mature flowers, and the petal/sepal abscission zone of mature siliques. The presence of GUS activity in guard cells, lateral roots, pollen grains, leaf vascular tissue, and internal cells of stipules and nectaries was not confirmed by in situ hybridizations, supporting previous observations that suggest that the reporter gene is subject to artifactual expression. These results are consistent with a role for the LTP1 gene product in some aspect of secretion or deposition of lipophilic substances in the cell walls of expanding epidermal cells and certain secretory tissues. The LTP1 promoter region contained sequences homologous to putative regulatory elements of genes in the phenylpropanoid biosynthetic pathway, suggesting that the expression of the LTP1 gene may be regulated by the same or similar mechanisms as genes in the phenylpropanoid pathway